Creative Leadership: Skills That Drive Change - Gerard J. Puccio, Mary C. Murdock, Marie Mance (Sage, 2007)
Successful leadership today relies heavily on an individual′s ability to effectively respond to and proactively drive change―in short, to be creative. This book helps readers enhance their creative talents and employ these skills as a leader. New to the Second Edition is an expanded discussion of the important role creativity plays in leadership, a more extensive account of the skills necessary to be an effective creative leader, a broader range of historical and contemporary examples, and enhanced graphics throughout that bring the Creative Problem Solving model to life visually.